PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD N 1 PENATIH TAHUN PELAJARAN 2020/2021 - I Wayan Darmayoga (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This study aims to determine the use of Picture and picture methods could increase the interest and learning achievements of science in fourth grade students of Elementary School number 1 Penatih in the academic year 2020/2021. This research consists of two cycles, each cycle consisting of four stages, namely planning, implementing actions, observing/evaluating, and reflecting. The subjects of this study were the fourth grade students of Elementary School number 1 Penatih, totally 34 people. The object of this study is the interest and learning achievements of Natural Sciences. The method of collecting data that used to this research is the test methods of collecting data on student learning achievements. Based on the result of research could explain the average percentage of student learning achievements of Social Science increased to 50% and the classical completeness increased to 40%. The use of Project Based Learning (PBL) methods support by visual media in the first cycle the average percentage of students' learning interest increased to 65%, and classical completeness reached 60%. With the improvement in cycle II the average percentage of interest in learning increased to 90%, and the classical completeness reached 85%.